Expression pattern of GLUT 1, 5, 8 and citrate synthase transcripts in buffalo (Bubalus bubalis) preimplantation embryos produced in vitro and derived in vivo. Issue 10 (17th August 2020) - Taru Sharma, Gutulla; Nath, Amar; Prasad, Shiv; Singhal, Sumit; Chandra, Vikash; Saikumar, Gutulla
Abstract: In vitro‐produced (IVP) embryos are reported to be developmentally lesser competent than in vivo‐derived (IVD) embryos and supposed to differ in the expression of genes related with glucose metabolism. So, the present study was conducted to analyse the expression pattern of GLUT 1, 5, 8 and citrate synthase ( CS ) in oocytes and embryos produced in vivo or in vitro in buffalo. IVD embryos were obtained from 18 superovulated buffaloes. IVP embryos were obtained from slaughterhouse‐derived oocytes subsequently subjected to in vitro fertilization and culture. Total RNA was isolated from different stages of oocytes (immature and in vitro matured) and embryos (8–16 cell to blastocysts of IVP embryos and morula to blastocysts of IVD embryos). Results demonstrated that the expression of GLUT1, GLUT 8 increased from 8 to 16 cells to blastocyst and was significantly ( p < .05) higher in IVP embryos. Expression of both genes was ( p < .05) higher in IVD than in IVP blastocysts; though GLUT5 transcripts were not detected at 8‐ to 16‐cell stage IVP embryos, significantly ( p < .05) higher transcripts were found at morula and blastocyst stages irrespective of embryo source with significantly ( p < .05) higher expression in IVD embryos compared to IVP embryos. No significant difference was observed in citrate synthase expression in embryos at morula stage irrespective of the embryo source while significantly ( p < .05) higher transcript level was observed at blastocyst stage with no difference between in vivo and in vitro embryos. It can be concluded that expression of GLUTs and CS is upregulated with progression of embryonic stage and expression is higher in in vivo embryos than in vitro counter parts; thus, it can be said that in vivo ‐ produced embryos are metabolically superior to in vitro embryos.